Blockchain technology adoption, architecture, and sustainable agri-food supply chains - Saurabh, Samant; Dey, Kushankur (Journal of cleaner production, 2021)
The emerging Information and Communication Technology play a vital role in electronic agriculture. The application of such technologies as blockchain, Internet-of-Things, wireless sensor networks, cloud computing, and machine learning can improve the agri-food supply chain efficiency and quality management. However, there is little evidence on the determinants of blockchain integrated ICTs adoption for the supply chain actors and their propensity to embrace and use such technologies. To bridge this research gap in the literature, we identify a few potential drivers of blockchain technology adoption, considering the grape wine supply chain and employing a rating-based conjoint analysis. The study finds that dis-intermediation, traceability, price, trust, compliance, and coordination and control in order of their relative importance and utilities can influence the supply chain actors’ adoption-intention decision processes. The adoption factors further rationalize the design for a modular, scalable, interoperable, and cost-effective architecture for supply chain integration and sustainability. [Display omitted] •We study technology adoption factors for grape wine supply chain using conjoint analysis.•Disintermediation, traceability, and price influence the actors’ adoption decisions.•We propose modular, interoperable, and cost-effective blockchain architecture.•Architecture improves enterprise performance and sustainable supply chain practices.